Comparative genomics of Rothia species reveals diversity in novel biosynthetic gene clusters and ecological adaptation to different eukaryotic hosts and host niches. Issue 9 (27th September 2022) - Oliveira, Isabela M. Fernandes de; Ng, Duncan Y. K.; van Baarlen, Peter; Stegger, Marc; Andersen, Paal Skytt; Wells, Jerry M.
Abstract : Rothia species are understudied members of the phylum Actinobacteria and prevalent colonizers of the human and animal upper respiratory tract and oral cavity. The oral cavity, including the palatine tonsils, is colonized by a complex microbial community, which compete for resources, actively suppress competitors and influence host physiology. We analysed genomic data from 43 new porcine Rothia isolates, together with 112 publicly available draft genome sequences of Rothia isolates from humans, animals and the environment. In all Rothia genomes, we identified biosynthetic gene clusters predicted to produce antibiotic non-ribosomal peptides, iron scavenging siderophores and other secondary metabolites that modulate microbe–microbe and potentially microbe–host interactions. In vitro overlay inhibition assays corroborated the hypothesis that specific strains produce natural antibiotics. Rothia genomes encode a large number of carbohydrate-active enzymes (CAZy), with varying CAZy activities among the species found in different hosts, host niches and environments. These findings reveal competition mechanisms and metabolic specializations linked to ecological adaptation of Rothia species in different hosts.